Carbon sequestration material as well as preparation method and application thereof

By using aluminum-doped iron mineral nanoparticles as carbon sequestration materials, the problem of insufficient soil organic carbon sequestration capacity is solved, and the effect of stabilizing organic carbon sequestration in different soil environments is achieved.

CN119799340AActive Publication Date: 2025-04-11GUANGDONG INST OF ECO ENVIRONMENT & SOIL SCI
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411771916.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-04-11
Estimated Expiration
2044-12-04

AI Technical Summary

Technical Problem

The prior art has shortcomings in improving the soil organic carbon sequestration capacity, especially after directly adding minerals with high crystallinity, organic carbon is easily released again, and pure nano-iron minerals may cause damage to the soil ecological environment.

Method used

Using aluminum-doped iron ore nanoparticles as carbon sequestration materials, nanoparticles with different aluminum doping amounts are prepared by regulating the hydrolysis rate of iron and aluminum, and their specific surface area and adsorption sites are improved, thereby enhancing the sequestration capacity of organic carbon.

Benefits of technology

It has achieved long-term and stable storage of organic carbon in soil environments with different pH, avoided the re-release of organic carbon, and had a small impact on the soil ecological environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005170461360000011
    Figure HDA0005170461360000011
  • Figure HDA0005170461360000021
    Figure HDA0005170461360000021
  • Figure HDA0005170461360000022
    Figure HDA0005170461360000022
Patent Text Reader

Abstract

The invention relates to the technical field of soil improvement, and discloses a carbon sequestration material as well as a preparation method and application thereof. The carbon sequestration material is aluminum-doped iron mineral nano-particles, the particle size of the particles is 2-8 nm, the specific surface area is 350-410 m < 2 > / g, and the particles are good in dispersity and have a good pore structure; aluminum is doped by replacing the position of iron in the structure, so that the specific surface area and adsorption sites of the material are improved, and the organic carbon immobilization capacity of the material is improved; the preparation raw materials of the carbon sequestration material are easy to obtain, the preparation method is simple, the reaction conditions are mild, materials with different aluminum doping amounts can be obtained by regulating and controlling the hydrolysis rate of ferric iron and aluminum ions, the formation of aggregates is reduced in the synthesis process, the operation is simple, and the efficiency is high; the soil carbon sequestration agent is applied to improvement of soil carbon sequestration capacity, has good organic carbon sequestration performance, can adapt to soil environments with different pH values, and can keep long-term stability of organic carbon sequestration under various environmental conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of soil improvement, and in particular to a carbon fixation material and a preparation method and application thereof. Background Art

[0002] As the largest carbon pool in the global terrestrial ecosystem, the soil organic carbon pool has a much higher carbon content than terrestrial vegetation and atmospheric carbon pools. Slight changes in the soil organic carbon pool will lead to large fluctuations in the concentration of carbon dioxide in the atmosphere. The ability of the soil to fix carbon largely determines the concentration of carbon dioxide in the atmosphere. Therefore, increasing soil carbon sequestration is an effective measure to reduce soil carbon emissions and help alleviate the global greenhouse effect. In addition, improving the organic carbon sequestration capacity in the soil can also help improve soil fertility and quality and promote crop growth. However, the dissolved organic carbon in the soil is highly mobile and easily degraded. Therefore, reducing the mobility of soil organic carbon and transforming it to a more stable state is the key to enhancing soil organic carbon sequestration and stability.

[0003] Aluminum and iron are the third and fourth most abundant elements in the earth's crust. They often exist in the form of complex minerals and have a great influence on the composition change and stability of soil organic carbon. A large number of studies have shown that iron and aluminum minerals play an important role in the fixation of organic carbon in sediments, frozen soils, forest soils and agricultural soils. The fixation of soil organic carbon can be divided into the following three ways: the first is the physical protection mechanism, that is, soil aggregates and organic carbon are embedded and blocked; the second is the chemical protection mechanism, that is, soil minerals fix soil organic carbon through van der Waals forces, high-order cation bond bridges and ligand exchange; the third is biochemical protection, that is, the refractory molecules in soil organic carbon resist decomposition by external microorganisms or free radicals. As an important component of soil minerals, soil active iron and aluminum minerals (such as ferrihydrite, allophane and iron and aluminum hydrate oxides) are the most common minerals in soil. They have high surface activity and often fix soil organic carbon by cation bridging, surface complexation, coordination exchange, etc., and the stability of soil organic carbon fixed in this way is the highest.

[0004] Based on this, a series of materials related to active iron-aluminum minerals have been developed to promote soil carbon sequestration. However, these materials generally have the following disadvantages: (1) Directly adding highly crystalline minerals to the soil has a weak ability to store organic carbon, and after the reduction reaction in the soil, most of the adsorbed organic carbon will be released, resulting in the re-release of the stored organic carbon into the soil in the short term; (2) It is difficult to find pure iron minerals in the soil. They generally exist in the form of iron-aluminum composite minerals. Directly adding pure iron minerals to the soil may cause damage to the local soil ecological environment, which is not conducive to the growth of crops. For example, CN 115746866A discloses a method for promoting soil carbon sequestration using nano-hematite. Nano-hematite is added to the soil to promote soil carbon fixation. Pure nano-hematite has a low specific surface area and weak adsorption of soil organic carbon. It is difficult to continue to play a role after adsorption saturation. Nano-hematite is prone to agglomeration after being applied to the soil, and its adsorption capacity is further reduced. In addition, applying a large amount of pure nano-iron minerals to the soil will also cause an imbalance in the iron-aluminum ratio in the soil, which is not conducive to crop growth. The synthesis conditions of pure nano-hematite are also relatively complex, and the synthesis cost is high, which is not suitable for large-scale promotion and use. Summary of the invention

[0005] The present invention aims to solve at least one of the above-mentioned technical problems existing in the prior art. To this end, one of the purposes of the present invention is to provide a carbon-fixing material; the second purpose of the present invention is to provide a method for preparing the carbon-fixing material; the third purpose of the present invention is to provide an application of the carbon-fixing material.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is:

[0007] A first aspect of the present invention provides a carbon-fixing material, wherein the carbon-fixing material is aluminum-doped iron mineral nanoparticles.

[0008] In some embodiments of the present invention, the doping amount of aluminum is less than 40 mol% of the total amount of aluminum and iron elements in the carbon-fixing material.

[0009] In some specific embodiments of the present invention, the doping amount of aluminum is less than or equal to 30 mol% of the total amount of aluminum and iron elements in the carbon-fixing material.

[0010] In some embodiments of the present invention, the particle size of the carbon-fixing material is 2-8 nm.

[0011] In some specific embodiments of the present invention, the particle size of the carbon-fixing material is 3-6 nm.

[0012] In some embodiments of the present invention, the specific surface area of ​​the carbon-fixing material is 350-410 m 2 / g.

[0013] In some specific embodiments of the present invention, the specific surface area of ​​the carbon-fixing material is 360-400m 2 / g.

[0014] In some embodiments of the present invention, the zero point charge of the carbon-fixing material is 7-10.

[0015] In some specific embodiments of the present invention, the zero point charge of the carbon-fixing material is 7-9.

[0016] In some embodiments of the present invention, the raw materials for preparing the carbon-fixing material include an aqueous solution of iron salt and an aqueous solution of aluminum salt.

[0017] In some specific embodiments of the present invention, the concentration of the iron salt aqueous solution is 0.4-0.6 mol / L.

[0018] In some specific embodiments of the present invention, the concentration of the aluminum salt aqueous solution is 0.4-0.6 mol / L.

[0019] In the present invention, since the grain sizes of iron atoms and aluminum atoms are similar, aluminum is doped by replacing the position of iron in the structure. Therefore, trivalent iron and trivalent aluminum are used as raw materials, and their co-hydrolysis rates are adjusted to obtain carbon-fixing materials with different aluminum doping amounts.

[0020] In some embodiments of the present invention, the iron salt aqueous solution is selected from one of an aqueous solution of ferric nitrate, an aqueous solution of ferric chloride, an aqueous solution of ferric acetate, and an aqueous solution of ferric citrate.

[0021] In some specific embodiments of the present invention, the aqueous solution of iron salt is an aqueous solution of ferric nitrate.

[0022] In some embodiments of the present invention, the aluminum salt aqueous solution is selected from one of aluminum nitrate solution, aluminum chloride solution and aluminum acetate solution.

[0023] In some specific embodiments of the present invention, the aluminum salt aqueous solution is an aluminum nitrate aqueous solution.

[0024] The second aspect of the present invention provides a method for preparing the carbon-fixing material according to the first aspect of the present invention, comprising the following steps:

[0025] The iron salt aqueous solution and the aluminum salt aqueous solution are mixed to obtain a suspension, the solid-liquid separation is performed, and the solid phase is collected to obtain the carbon-fixing material.

[0026] In some embodiments of the present invention, the pH of the suspension is 7-8.

[0027] In some specific embodiments of the present invention, the pH of the suspension is 7.3-7.5.

[0028] In some embodiments of the present invention, an alkali solution is added dropwise to adjust the pH of the suspension.

[0029] In some embodiments of the present invention, the alkali source of the alkali solution comprises an alkali metal hydroxide.

[0030] In some specific embodiments of the present invention, the alkali source of the alkali solution is selected from at least one of potassium hydroxide and sodium hydroxide.

[0031] In some embodiments of the present invention, the concentration of the alkali solution is 0.8-1.2 mol / L.

[0032] In some embodiments of the present invention, the dropping speed of the alkali solution is 0.8-1.2 mL / min.

[0033] In some embodiments of the present invention, the process of mixing the aqueous solution of iron salt and the aqueous solution of aluminum salt is assisted by stirring.

[0034] In some embodiments of the present invention, the stirring speed is 200-240 r / min, and the stirring time is 25-35 min.

[0035] In some embodiments of the present invention, the process of adjusting the pH of the suspension is assisted by stirring.

[0036] In some embodiments of the present invention, the stirring speed is 200-240 r / min, and the stirring time is 20-30 h.

[0037] In some embodiments of the present invention, the rotation speed of the centrifugal separation is 5500-6500 r / min.

[0038] In some embodiments of the present invention, after the centrifugal separation, the steps of washing and drying are further included to obtain the carbon-fixing material.

[0039] The third aspect of the present invention provides the use of the carbon fixation material described in the first aspect of the present invention in soil improvement.

[0040] In some embodiments of the present invention, the soil improvement includes enhancing the soil carbon sequestration capacity.

[0041] In some embodiments of the present invention, the mass ratio of the carbon-fixing material to the soil is 1:(20-45).

[0042] In some specific embodiments of the present invention, the mass ratio of the carbon fixation material to the soil is 1:(25-35).

[0043] In some embodiments of the invention, the pH of the soil is 3-10.

[0044] In some specific embodiments of the present invention, the pH of the soil is 4-9.

[0045] Compared with the prior art, the present invention has the following beneficial effects:

[0046] 1) The carbon-fixing material provided by the present invention is an aluminum-doped iron mineral nanoparticle with a particle size of 2-8 nm and a specific surface area of ​​350-410 m 2 / g, the particles have good dispersion and good pore structure; aluminum is doped by replacing the position of iron in the structure, which increases the specific surface area and adsorption sites of the material and improves the organic carbon sequestration capacity of the material;

[0047] 2) The raw materials for preparing the carbon-fixing material provided by the present invention are readily available, the preparation method is simple, the reaction conditions are mild, and materials with different aluminum doping amounts can be obtained by regulating the hydrolysis rates of trivalent iron and aluminum ions. The formation of agglomerates is reduced during the synthesis process, the operation is simple, the efficiency is high, and the obtained carbon-fixing material has high purity and is free of other impurity minerals;

[0048] 3) The carbon fixation material provided by the present invention is used to improve the carbon sink capacity of soil, has good organic carbon sequestration performance, can adapt to soil environments with different pH values, and can maintain long-term stability of organic carbon sequestration under a variety of environmental conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 It is a transmission electron microscope image of the carbon-fixing material in Example 1-4;

[0050] Figure 2 is the X-ray diffraction pattern of the carbon-fixing material in Examples 1-4;

[0051] Figure 3 is a graph showing the relationship between the unit cell parameters of the carbon-fixing material and the aluminum doping amount in Examples 1-4;

[0052] Figure 4 is the X-ray photoelectron spectrum of Fe 2p (a) and Al 2p (b) of the carbon-fixing materials in Examples 1-4;

[0053] Figure 5 is a relationship diagram of soluble iron and soluble aluminum in the carbon-fixing material in Example 2-4;

[0054] Figure 6 is the zero-point charge of the carbon-fixing material in Examples 1-4;

[0055] Figure 7 is the specific surface area of ​​the carbon-fixing material in Examples 1-4;

[0056] Figure 8 is the X-ray photoelectron spectrum of the carbon-fixing material O1s in Examples 1-4;

[0057] Fig. 9 is the adsorbed oxygen of the carbon-fixing material in Examples 1-4;

[0058] Fig.10 The test results of the organic carbon sequestration performance of the carbon sequestration material in Experimental Example 1;

[0059] Fig.11 These are the stability test results of the carbon-fixing material in fixing organic carbon in Experimental Example 2. DETAILED DESCRIPTION

[0060] The present invention is further described in detail below by specific examples. The raw materials, reagents or devices used in the examples can be obtained from conventional commercial sources or by prior art methods unless otherwise specified. Unless otherwise specified, the experiments or test methods are conventional methods in the art.

[0061] In the following examples, iron nitrate aqueous solution and aluminum nitrate aqueous solution were used as raw materials to prepare carbon-fixing materials, and sodium hydroxide solution was used to adjust the pH of the solution. The preparation process of each solution is as follows:

[0062] 1) Weigh 30.30 g of solid ferric nitrate nonahydrate into a beaker, add 150 mL of deionized water to fully dissolve it, and prepare 150 mL of a 0.5 mol / L ferric ion solution;

[0063] 2) Weigh 28.1 g of aluminum nitrate nonahydrate solid into a beaker, add 150 mL of deionized water to fully dissolve it, and prepare 150 mL of a 0.5 mol / L trivalent aluminum ion solution;

[0064] 3) Weigh 4 g of sodium hydroxide solid into a 250 mL beaker, add 100 mL of deionized water to prepare 100 mL of 1 mol / L sodium hydroxide solution.

[0065] The water used in the examples was all deionized water, and the reagents used, including ferric nitrate nonahydrate, aluminum nitrate nonahydrate, sodium hydroxide, and sodium chloride, were purchased from Sinopharm Reagents and were all analytically pure.

[0066] Example 1

[0067] This embodiment prepares a carbon-fixing material, and the steps are as follows:

[0068] S1. Take 14 mL of 0.5 mol / L ferric ion solution and add it to a 100 mL glass beaker, place it on a magnetic stirrer, add 70 mL of deionized water, and stir the solution at a speed of 200 r / min for 30 min to obtain a mixed solution;

[0069] S2. Add sodium hydroxide solution to the mixed solution at a rate of 1 mL / min. As the sodium hydroxide solution is added, the color of the solution gradually turns red and becomes turbid. Continue to add until the pH value of the solution rises to 7.5. Continue stirring for 24 h, during which the pH value of the solution is kept constant at 7.5.

[0070] S3, centrifuge the above solution at a speed of 6000r / min, pour off the supernatant after the precipitation, then add the same volume of deionized water, mix thoroughly and centrifuge again, repeat this step three times to remove excess ions on the solid surface;

[0071] S4. The wet solid obtained after washing is placed in a freeze dryer for dehydration and drying, and taken out after 24 hours to obtain iron mineral nanoparticles without aluminum doping, which are recorded as 0AlFh.

[0072] Example 2

[0073] This embodiment prepares a carbon-fixing material, and the steps are as follows:

[0074] S1. Take 12.6 mL of 0.5 mol / L trivalent iron ion solution and add it into a 100 mL glass beaker, place it on a magnetic stirrer, first add 1.4 mL of 0.5 mol / L trivalent aluminum ion solution, then add 70 mL of deionized water, and stir the solution at a speed of 200 r / min for 30 min to obtain a mixed solution;

[0075] S2. Add sodium hydroxide solution to the mixed solution at a rate of 1 mL / min. As the sodium hydroxide solution is added, the color of the solution gradually turns red and becomes turbid. Continue to add until the pH value of the solution rises to 7.5. Continue stirring for 24 h, during which the pH value of the solution is kept constant at 7.5.

[0076] S3, centrifuge the above solution at a speed of 6000r / min, pour off the supernatant after the precipitation, then add the same volume of deionized water, mix thoroughly and centrifuge again, repeat this step three times to remove excess ions on the solid surface;

[0077] S4. The wet solid obtained after washing is placed in a freeze dryer for dehydration and drying. After 24 hours, it is taken out to obtain aluminum-doped iron mineral nanoparticles. The aluminum doping amount is 10 mol% of the total amount of iron and aluminum in the nanoparticles, recorded as 10AlFh.

[0078] Example 3

[0079] This embodiment prepares a carbon-fixing material, and the steps are as follows:

[0080] S1. Take 11.2 mL of 0.5 mol / L trivalent iron ion solution and add it into a 100 mL glass beaker, place it on a magnetic stirrer, first add 2.8 mL of 0.5 mol / L trivalent aluminum ion solution, then add 70 mL of deionized water, and stir the solution at a speed of 200 r / min for 30 min to obtain a mixed solution;

[0081] S2. Add sodium hydroxide solution to the mixed solution at a rate of 1 mL / min. As the sodium hydroxide solution is added, the color of the solution gradually turns red and becomes turbid. Continue to add until the pH value of the solution rises to 7.5. Continue stirring for 24 h, during which the pH value of the solution is kept constant at 7.5.

[0082] S3, centrifuge the above solution at a speed of 6000r / min, pour off the supernatant after the precipitation, then add the same volume of deionized water, mix thoroughly and centrifuge again, repeat this step three times to remove excess ions on the solid surface;

[0083] S4. The wet solid obtained after washing is placed in a freeze dryer for dehydration and drying. After 24 hours, it is taken out to obtain aluminum-doped iron mineral nanoparticles. The aluminum doping amount is 20 mol% of the total amount of iron and aluminum in the nanoparticles, recorded as 20AlFh.

[0084] Example 4

[0085] This embodiment prepares a carbon-fixing material, and the steps are as follows:

[0086] S1. Take 9.8 mL of 0.5 mol / L trivalent iron ion solution and add it to a 100 mL glass beaker, place it on a magnetic stirrer, first add 4.2 mL of 0.5 mol / L trivalent aluminum ion solution, then add 70 mL of deionized water, and stir the solution at a speed of 200 r / min for 30 min to obtain a mixed solution;

[0087] S2. Add sodium hydroxide solution to the mixed solution at a rate of 1 mL / min. As the sodium hydroxide solution is added, the color of the solution gradually turns red and becomes turbid. Continue to add until the pH value of the solution rises to 7.5. Continue stirring for 24 h, during which the pH value of the solution is kept constant at 7.5.

[0088] S3, centrifuge the above solution at a speed of 6000r / min, pour off the supernatant after the precipitation, then add the same volume of deionized water, mix thoroughly and centrifuge again, repeat this step three times to remove excess ions on the solid surface;

[0089] S4. The wet solid obtained after washing is placed in a freeze dryer for dehydration and drying. After 24 hours, it is taken out to obtain aluminum-doped iron mineral nanoparticles. The aluminum doping amount is 30 mol% of the total amount of iron and aluminum in the nanoparticles, recorded as 30AlFh.

[0090] Example 5

[0091] This embodiment prepares a carbon-fixing material, and the steps are as follows:

[0092] S1. Take 9.52 mL of 0.5 mol / L trivalent iron ion solution and add it to a 100 mL glass beaker, place it on a magnetic stirrer, first add 4.48 mL of 0.5 mol / L trivalent aluminum ion solution, then add 70 mL of deionized water, and stir the solution at a speed of 200 r / min for 30 min to obtain a mixed solution;

[0093] S2. Add sodium hydroxide solution to the mixed solution at a rate of 1 mL / min. As the sodium hydroxide solution is added, the color of the solution gradually turns red and becomes turbid. Continue to add until the pH value of the solution rises to 7.5. Continue stirring for 24 h, during which the pH value of the solution is kept constant at 7.5.

[0094] S3, centrifuge the above solution at a speed of 6000r / min, pour off the supernatant after the precipitation, then add the same volume of deionized water, mix thoroughly and centrifuge again, repeat this step three times to remove excess ions on the solid surface;

[0095] S4. The wet solid obtained after washing is placed in a freeze dryer for dehydration and drying. After 24 hours, it is taken out to obtain aluminum-doped iron mineral nanoparticles. The aluminum doping amount is 32 mol% of the total amount of iron and aluminum in the nanoparticles, recorded as 32AlFh.

[0096] Example 6

[0097] This embodiment prepares a carbon-fixing material, and the steps are as follows:

[0098] S1. Take 9.4 mL of 0.5 mol / L trivalent iron ion solution and add it to a 100 mL glass beaker, place it on a magnetic stirrer, first add 5.6 mL of 0.5 mol / L trivalent aluminum ion solution, then add 70 mL of deionized water, and stir the solution at a speed of 200 r / min for 30 min to obtain a mixed solution;

[0099] S2. Add sodium hydroxide solution to the mixed solution at a rate of 1 mL / min. As the sodium hydroxide solution is added, the color of the solution gradually turns red and becomes turbid. Continue to add until the pH value of the solution rises to 7.5. Continue stirring for 24 h, during which the pH value of the solution is kept constant at 7.5.

[0100] S3, centrifuge the above solution at a speed of 6000r / min, pour off the supernatant after the precipitation, then add the same volume of deionized water, mix thoroughly and centrifuge again, repeat this step three times to remove excess ions on the solid surface;

[0101] S4. The wet solid obtained after washing is placed in a freeze dryer for dehydration and drying. After 24 hours, it is taken out to obtain aluminum-doped iron mineral nanoparticles. The aluminum doping amount is 40 mol% of the total amount of iron and aluminum in the nanoparticles, recorded as 40AlFh.

[0102] Example 7

[0103] This embodiment prepares a carbon-fixing material, and the steps are as follows:

[0104] S1. Take 3.8 mL of 0.5 mol / L trivalent iron ion solution and add it into a 100 mL glass beaker, place it on a magnetic stirrer, first add 11.2 mL of 0.5 mol / L trivalent aluminum ion solution, then add 70 mL of deionized water, and stir the solution at a speed of 200 r / min for 30 min to obtain a mixed solution;

[0105] S2. Add sodium hydroxide solution to the mixed solution at a rate of 1 mL / min. As the sodium hydroxide solution is added, the color of the solution gradually turns red and becomes turbid. Continue to add until the pH value of the solution rises to 7.5. Continue stirring for 24 h, during which the pH value of the solution is kept constant at 7.5.

[0106] S3, centrifuge the above solution at a speed of 6000r / min, pour off the supernatant after the precipitation, then add the same volume of deionized water, mix thoroughly and centrifuge again, repeat this step three times to remove excess ions on the solid surface;

[0107] S4. The wet solid obtained after washing is placed in a freeze dryer for dehydration and drying. After 24 hours, it is taken out to obtain aluminum-doped iron mineral nanoparticles. The aluminum doping amount is 80 mol% of the total amount of iron and aluminum in the nanoparticles, recorded as 80AlFh.

[0108] Example 8

[0109] This embodiment prepares a carbon-fixing material, and the steps are as follows:

[0110] S1. Take 15 mL of 0.5 mol / L trivalent aluminum ion solution and add it into a 100 mL glass beaker, place it on a magnetic stirrer, add 70 mL of deionized water, and stir the solution at a speed of 200 rpm for 30 min to obtain a mixed solution;

[0111] S2. Add sodium hydroxide solution to the mixed solution at a rate of 1 mL / min. As the sodium hydroxide solution is added, the color of the solution gradually turns red and becomes turbid. Continue to add until the pH value of the solution rises to 7.5. Continue stirring for 24 h, during which the pH value of the solution is kept constant at 7.5.

[0112] S3, centrifuging the above solution at a speed of 6000 rpm, pouring off the supernatant after the precipitation, and then adding the same volume of deionized water, mixing thoroughly and centrifuging again, repeating this step three times to remove excess ions on the solid surface;

[0113] S4. The wet solid obtained after washing is placed in a freeze dryer for dehydration and drying, and taken out after 24 hours to obtain aluminum mineral nanoparticles, which are recorded as 100AlFh.

[0114] Material characterization

[0115] The carbon-fixing materials prepared in Examples 1-8 were subjected to transmission electron microscopy characterization, X-ray diffraction characterization and refinement, X-ray photoelectron spectroscopy and specific surface area characterization, and mineral acid dissolution experiments. The specific methods are as follows:

[0116] 1) Transmission electron microscopy characterization

[0117] Take 5 μL of the carbon-fixing material synthesized in Examples 1-8 and disperse them in an acetone solution respectively, and ultrasonicate for 25 minutes to make it evenly dispersed. The resulting suspension is used to prepare samples for transmission electron microscopy analysis. In order to prevent changes in the solid phase components during the ultrasonication process, the entire ultrasonication process is carried out in water at 25°C. The suspension obtained after ultrasonication is added dropwise to an ultra-thin C film supported by a 200-mesh copper mesh, and then placed under infrared light for drying. The morphology of the aluminum-iron mineral nanoparticle carbon-fixing material was analyzed using a transmission electron microscope (JEOL JEM 2100). In order to ensure reliable results, multiple areas of the sample were selected for analysis.

[0118] 2) X-ray diffraction characterization and refinement

[0119] The solid samples obtained after freeze-drying in Examples 1-8 were placed in an agate mill and ground, and the solid powder was collected and placed in a 1.5 mL centrifuge tube. The solid powder was analyzed using an X-ray diffractometer (XRD, Bruker D8 Advance). The instrument was equipped with Cu Kα, and the diffraction wavelength λ was 0.15418 nm. During the testing of all samples, the instrument tube voltage was set to 40 kV, the tube flow was set to 40 mA, the step length was set to 0.02°, the step speed was set to 2° / min, and the collection range of all diffraction spectra was set to 10°-70°. The crystal structure of the test sample was refined using TOPAS software, and the unit cell parameters of the initial sample were referenced to pure ferrihydrite. The X-ray diffraction pattern of the sample was continuously fitted until Rwp <10%, and the standard deviation of the unit cell parameters is approximately 0.001.

[0120] 3) X-ray photoelectron spectroscopy and specific surface area characterization

[0121] The X-ray photoelectron spectra of Fe 2p, Al 2p and O1s of the aluminum-iron mineral nanoparticle carbon-fixing materials in Examples 1-8 were measured using an X-ray photoelectron spectrometer (Thermo Scientific K-Alpha). Before collecting the X-ray photoelectron spectra, the instrument was energy calibrated using the binding energy of C1s to obtain accurate data. In order to quantify the O form in the aluminum-iron mineral nanoparticles, the X-ray photoelectron spectrum of O1s was fitted using Peakfit software (v.4.12) to obtain the percentage of surface adsorbed water, adsorbed oxygen and lattice oxygen.

[0122] In order to determine the specific surface area of ​​the aluminum-containing iron mineral nanoparticle carbon-fixing materials doped with different aluminum, 30 mg of the solid samples in Examples 1-8 were weighed in glass tubes and placed in a vacuum (10 -3 mbar) for 72 h to remove moisture, gas and impurities adsorbed on the surface. Then, the sample was analyzed using a specific surface area analyzer (Micromeritics3000) in a nitrogen atmosphere at 77 K, and the adsorption and desorption isotherms in the partial pressure region of 0.01 to 0.995P / P0 (including 25 adsorption points and 24 desorption points) were collected. The adsorption and desorption curves were analyzed using the BET equation to obtain the specific surface area of ​​the solid sample.

[0123] 4) Mineral acid dissolution test

[0124] At room temperature (25°C), 100 mg of the carbon-fixing material in Examples 1-8 was weighed in a 250 mL glass conical flask, and then 100 mL of 1 mol / L HCl was added thereto to dissolve the mineral. Sampling was performed at different reaction time points, and 5 mL of the suspension sample was taken out from the conical flask each time, and the resulting suspension was immediately filtered with a 0.22 μm nylon filter membrane to collect the filtrate. The concentrations of Fe and Al in the filtrate were determined using an inductively coupled plasma optical emission spectrometer (ICP-OES, Agilent 5800) to determine the dissolution kinetics of the carbon-fixing material.

[0125] Through characterization and analysis such as transmission electron microscopy, it was found that when the aluminum doping amount in the carbon-fixing material is greater than 30% of the total molar amount of iron and aluminum, hydroalphite impurities will appear in the material, and the particle size is larger, which is a non-nanoparticle size, and the specific surface area, zero-point charge, and percentage of adsorbed oxygen of the carbon-fixing material all show a downward trend. Therefore, it is best that the aluminum doping amount in the carbon-fixing material is less than or equal to 30% of the total molar amount of iron and aluminum.

[0126] Figure 1 is a transmission electron microscope image of the carbon-fixing material in Examples 1-4, wherein: Figure 1 (a) is a transmission electron microscope image of the carbon-fixing material 0AlFh in Example 1, Figure 1 (b) is a transmission electron microscope image of the carbon-fixing material 10AlFh in Example 2, Figure 1 (c) is a transmission electron microscope image of the carbon-fixing material 20AlFh in Example 3, Figure 1 (d) is a transmission electron microscope image of the carbon-fixing material 30AlFh in Example 4. Figure 1 It can be seen that the carbon-fixing materials in Examples 1-4 are nano-sized, with a particle size of about 3-6 nm, good particle dispersibility, and a good pore structure.

[0127] Figure 2 is the X-ray diffraction pattern of the carbon-fixing material in Examples 1-4, Figure 2 It can be seen that no other impurity minerals appear in the carbon-fixing materials in Examples 1-4, and the synthesized nanomaterials have a high purity.

[0128] Figure 3 is a graph showing the relationship between the unit cell parameters of the carbon-fixing material and the aluminum doping amount in Examples 1-4, wherein: Figure 3 (a) is the relationship between the unit cell parameter a and the aluminum doping amount. Figure 3 (b) is the relationship between the unit cell parameter c and the aluminum doping amount, Figure 3 It can be seen that with the increase of aluminum doping amount, the unit cell parameters of carbon-fixing materials gradually decrease.

[0129] Figure 4 is the X-ray photoelectron spectrum of Fe 2p (a) and Al 2p (b) of the carbon-fixing materials in Examples 1-4, Figure 4 It can be seen that with the increase of aluminum dosage in the material synthesis process, the aluminum content in the carbon-fixing material gradually increases and the iron content gradually decreases.

[0130] Figure 5 is a relationship diagram of soluble iron and soluble aluminum in the carbon-fixing material of Example 2-4, Figure 5 It can be seen that since the grain sizes of iron atoms and aluminum atoms are similar, the aluminum in the carbon-fixing material is doped by replacing the position of iron in the structure. The doping of aluminum in iron mineral nanoparticles helps to increase the specific surface area and adsorption sites of the material, which is beneficial to improving the storage capacity of organic carbon.

[0131] Figure 6 is the zero-point charge of the carbon-fixing material in Examples 1-4, Figure 6 It can be seen that with the increase of aluminum doping, the zero-point charge of the carbon-fixing material gradually increases, and the zero-point charge increases from 7.26 to 8.96 when the doping amount increases from 0 to 30 mol%. Since organic carbon is negatively charged, the increase in zero-point charge increases the electrostatic attraction between minerals and organic matter, and promotes the adsorption of organic matter by minerals.

[0132] Figure 7 is the specific surface area of ​​the carbon-fixing material in Examples 1-4, Figure 7 It can be seen that with the increase of aluminum doping amount, the specific surface area of ​​carbon-fixing materials gradually increases. When the doping amount increases from 0 to 30 mol%, the specific surface area increases from 362 m 2 / g increased to 397m 2 / g.

[0133] Figure 8 is the X-ray photoelectron spectrum of the carbon-fixing material O1s in Examples 1-4, Fig. 9 is the adsorbed oxygen of the carbon-fixing material in Examples 1-4, Figure 8 and Fig. 9 It can be seen that with the increase of aluminum doping amount, the adsorbed oxygen of carbon-fixing materials increases, and the adsorption sites increase from 39.7% to 62.5% during the process of doping amount from 0 to 30 mol%. The increase of specific surface area and adsorption sites can promote the surface adsorption of aluminum-iron mineral nanoparticles carbon-fixing materials and organic matter, and increase the adsorption amount.

[0134] Test Example 1

[0135] 1) Extraction of soil dissolved organic carbon:

[0136] Weigh 10g of paddy field soil into a 100mL polytetrafluoroethylene bottle, then add 50mL of deionized water, place the polytetrafluoroethylene bottle on an oscillator, set the speed to 220r / min, and oscillate for 72h; after the oscillation, transfer the soil-water mixture to a 50mL centrifuge tube and centrifuge at a speed of 6000r / min for 20min; use a 0.45μm polyethersulfone filter membrane to filter the supernatant after centrifugation to remove other impurities, collect the filtrate in a brown glass bottle, which is the soil dissolved organic carbon solution, and store it in a refrigerator at 4°C.

[0137] 2) Test on the sequestration performance of carbon-fixing materials on soil dissolved organic carbon:

[0138] Take 4 100mL serum bottles, numbered 1-4, and add 47mL 0.01mol / L NaCl and 3mL 50mg C / L soil dissolved organic carbon solution, and then add 0.02g carbon fixation material prepared in Examples 1-4. The substances in the bottle are fully mixed to obtain a suspension, and the pH of the suspension is kept stable at 7.0 by adding 0.1mol / L HCl or 0.1mol / L NaOH, respectively. Then all serum bottles are placed in a constant temperature shaker and shaken at a speed of 220r / min. Fully shake for 72h at 25°C in the dark to ensure that adsorption equilibrium is reached. Each experimental condition is repeated three times.

[0139] All the suspension samples after the reaction were placed in a centrifuge at a speed of 6000r / min and centrifuged for 10min, and then the supernatants of different treatment groups were filtered using a 0.45μm polyethersulfone filter membrane to collect the supernatants. In order to avoid precipitation during sample storage and testing, 50μL 6.05mol / L HCl was added to all the obtained supernatants. After the supernatants of the samples of different treatment groups were collected, the concentration of dissolved organic carbon in all supernatants was uniformly determined using a total organic carbon analyzer (TOC-L, Shimadzu, Japan).

[0140] Fig.10 is the test result of the organic carbon sequestration performance of the carbon sequestration material in Experimental Example 1, wherein: Fig.10 (a) is the organic carbon concentration in the liquid phase after adsorption equilibrium, Fig.10 (b) is the organic carbon concentration in the solid phase after adsorption equilibrium, given by Fig.10 It can be seen that when the soil organic carbon sequestration performance test was carried out on the carbon-fixing materials in Examples 1-4, as the aluminum doping amount in the material increased from 0 to 30 mol%, the organic carbon content in the liquid phase decreased from 21.16 mg / L to 12.03 mg / L, while the solid phase organic carbon content increased from 192.29 mg C / g to 265.42 mg C / g, indicating that after aluminum doping, more active soil organic carbon was adsorbed by the aluminum-iron mineral nanoparticle carbon-fixing material, and its mobility was significantly reduced, which promoted the effective sequestration of dissolved organic carbon. Moreover, with the increase of aluminum doping (≤30 mol%), the sequestration performance of dissolved organic carbon in the soil gradually improved.

[0141] Test Example 2

[0142] 1) Prepare the reaction solution:

[0143] Take 4 100mL serum bottles, numbered 1-4, add 47mL 0.01mol / L NaCl and 3mL 50mg C / L soil dissolved organic carbon solution in Experimental Example 1 into each bottle, then add 0.4g of carbon fixation material prepared in Examples 1-4 into bottles 1-4 respectively, mix the substances in the bottles thoroughly to obtain a suspension, keep the pH of the suspension stable at 7.0 by adding 0.1mol / L HCl or 0.1mol / LNaOH respectively, then place all the serum bottles in a constant temperature shaker for oscillation, set the speed to 220r / min, and fully oscillate for 72h at 25℃ in the dark to ensure that adsorption equilibrium is reached, and repeat each experimental condition three times.

[0144] After adsorption equilibrium, the suspension was filtered using a 0.45 μm polyethersulfone filter membrane, and then the solid phase trapped on the filter membrane was washed 5 times with deionized water to ensure that excess ions and other impurities were washed away, and then naturally dried under natural ventilation conditions, and the solid was collected to obtain a composite precipitate. The composite precipitate obtained after the adsorption reaction was divided into 2 parts, one for determining the content of fixed organic carbon in the solid phase, and the other for verifying the release of organic carbon fixed by the carbon-fixing material in soil solutions of different pH values.

[0145] 2) Stability test of organic carbon after fixation:

[0146] Three paddy field soils with different pH were selected, located in Heshan City, Guangdong Province, Daye City, Hubei Province, and Panzhihua City, Sichuan Province. The pH of the three soils was 4.3, 6.5, and 8.1, respectively. The extracts of the three soils were used to conduct an organic carbon fixation stability experiment on carbon fixation materials. Weigh 25g of each of the three soils in a conical flask, add 250mL of deionized water, shake and extract at a rate of 220r / min for 3h, then let it stand for 15min, and absorb 220mL of the upper solution of the conical flask, which is the soil extract.

[0147] 50 mL of soil extract was taken and placed in a 100 mL serum bottle, and 0.2 g of the dried composite precipitate was added to each treatment group, and the blank group was not treated. On the 120th day, the organic carbon content in the solution of the system was measured, and the difference between the organic carbon in the solution of the treatment group and the blank group was the release of organic carbon from the carbon-fixing material.

[0148] Fig.11 The stability test results of the carbon fixation material fixing organic carbon in Experimental Example 2, wherein: Fig.11 (a) Fig.11 (b) Fig.11 (c) represent soil samples from Heshan City, Guangdong Province (pH = 4.3), Daye City, Hubei Province (pH = 6.5), and Panzhihua City, Sichuan Province (pH = 8.1). Fig.10It can be seen that in the experiment of actual soil samples, in three different soil solutions, organic carbon can remain stable for a long time in the composite precipitation of carbon-fixing materials. In the slightly acidic soil solution in Heshan City, Guangdong Province, after 120 days of cultivation, 97.2%-98.4% of organic carbon was fixed in the synthetic carbon-fixing material, and only 1.6%-2.8% of dissolved organic carbon was released; in the slightly neutral soil solution in Daye, Hubei Province, after 120 days of cultivation, the content of organic carbon fixed in the carbon-fixing material accounted for 96.1%-97.8% of the total sequestration, and only 2.2%-3.9% of dissolved organic carbon was released; in the slightly alkaline soil solution in Panzhihua City, Sichuan Province, after 120 days of cultivation, the content of organic carbon fixed in the material accounted for 95%-97.2% of the total sequestration, and only 2.8%-5% of dissolved organic carbon was released. The results of the above long-term continuous cultivation experiments show that the originally fixed active organic carbon can be stably fixed by aluminum-iron mineral nanoparticle carbon-fixing materials for a long time. In addition, in soils with different pH values, the higher the aluminum doping content in the carbon fixation material used, the lower the dissolved organic carbon content released after the incubation, indicating that the stored active organic carbon is more stable.

Claims

1. A carbon-fixing material, characterized in that: The carbon-fixing material is aluminum-doped iron mineral nanoparticles.

2. The carbon-fixing material according to claim 1, characterized in that: The doping amount of aluminum is less than 40 mol% of the total amount of aluminum and iron elements in the carbon-fixing material.

3. The carbon-fixing material according to claim 1, characterized in that: The particle size of the carbon-fixing material is 2-8 nm; And / or, the specific surface area of ​​the carbon-fixing material is 350-410m 2 / g.

4. The carbon-fixing material according to any one of claims 1 to 3, characterized in that: The raw materials for preparing the carbon-fixing material include an aqueous solution of iron salt and an aqueous solution of aluminum salt.

5. The method for preparing the carbon-fixing material according to claim 4, characterized in that: The following steps are involved: The iron salt aqueous solution and the aluminum salt aqueous solution are mixed to obtain a suspension, the solid-liquid separation is performed, and the solid phase is collected to obtain the carbon-fixing material.

6. The preparation method according to claim 5, characterized in that: The pH of the suspension is 7-8.

7. Use of the carbon-fixing material according to any one of claims 1 to 4 in soil improvement.

8. The use according to claim 7, characterized in that: The soil improvement includes enhancing the soil carbon sequestration capacity.

9. The use according to claim 7, characterized in that: The mass ratio of the carbon fixation material to the soil is 1:(20-45).

10. The use according to claim 7, characterized in that: The pH of the soil is 3-10.

Citation Information

Patent Citations

  • Method for promoting soil carbon sequestration through biochar

    CN115746866A

  • Metal-doped oxyhydroxide catalyst and preparation method and application thereof

    CN101658789A

  • Soil or ground reinforcement treatment method

    CN1088650A

  • Iron-aluminum-carbon composite catalytic material, preparation method and organic wastewater degradation method

    CN112439417A

  • Soil amendment for improving stability of soil aggregate and preparation method of soil amendment

    CN116694331A